The National Athletic Treatment, Injury and Outcomes Network (NATION): Methods of the surveillance program, 2011-2012 through 2013-2014 - Dompier, T. P.; Marshall, S. W.; Kerr, Z. Y.; Hayden, R. (Journal of Athletic Training, 2015)
Context: Previous epidemiologic researchers have examined time-loss (TL) injuries in high school student-athletes, but little is known about the frequency of non-time-loss (NTL) injuries in these athletes.